Authority and freedom in the thought of Lamberto Borghi - Baldacci, Massimo (Rivista di Storia dell’Educazione, 2023)
This paper examines Lamberto Borghi’s book Education and Authority in Modern Italy. In the first part, we describe the historical period in which this work was published. In the second part, we analyze its central theses. In the third part, we discuss the present significance of this work.